Lithium‐Ion Batteries: Cooling Induced Surface Reconstruction during Synthesis of High‐Ni Layered Oxides (Adv. Energy Mater. 43/2019). Issue 43 (20th November 2019) - Zhang, Ming‐Jian; Hu, Xiaobing; Li, Maofan; Duan, Yandong; Yang, Luyi; Yin, Chong; Ge, Mingyuan; Xiao, Xianghui; Lee, Wah‐Keat; Ko, Jun Young Peter; Amine, Khalil; Chen, Zonghai; et al.
Abstract : High‐nickel layered oxides are promising cathode candidates for high energy density Li‐ion batteries. However, as Ni loading increases, synthetic control of structure/stoichiometry, especially at the surface, becomes a challenge. The work presented in article number 1901915 by Jianming Bai, Feng Pan, Feng Wang, and co‐workers, through in situ X‐ray study into the synthesis of LiNi0.7 Mn0.15 Co0.15 O2 coupled with surface analysis, reveals cooling‐induced surface reconstruction, thereby enabling rational design of synthesis to improve the surface properties of synthesized materials.